Yahoo Web Search

  1. Ad
    related to: K
  1. ...you have written is evaluated like this: .030 = .22*(e^(- k ))*(.005) I think you intended the exponent to be ((- k )*.005) so you should...

    1 Answers · Science & Mathematics · 28/09/2013

  2. K (periodic table symbol for potassium). the general formula ( K ,AL)Si3O8 where the relative amounts of K and Al can vary to produce different types of feldspar. K -...

    2 Answers · Science & Mathematics · 14/12/2010

  3. You can't. You have to know what k is. That said, if you have other conditions which...like: (3x + m)(x + n) where m and n are integers, and: mn = k m + 3n = 16 ==> m = 16 - 3n k = n(16 - 3n) = 16n - 3n² So, pick...

    2 Answers · Science & Mathematics · 01/08/2008

  4. k = 0 let (x1,y1)=(3,7) (x2,y2)=(2, k ) (x3,y3)=(9,1) Apply distance formula. and equate the two...solve the equation by substitution the values i.e. (3-2)^2 + (7- k )^2 = (9-2)^2 + (1- k ) ^2 now solve it ..... implies k =0...

    1 Answers · Science & Mathematics · 12/05/2010

  5. K actually equals Kilometers (Kelvins is a measure of... (which is not really a standard velocity unit) However in K /s (or kilometers per second)....is would be 0.780 K ...

    3 Answers · Cars & Transportation · 03/11/2010

  6. k -on episode 1: http://www.animeseason.com/ k -on-episode-1/ http://www.gogoanime.com/ k -on-episode-1 k -on season 2 episode1: http://www.animeseason.com/ k -on-2nd-season-episode-1/# http://www.gogoanime.com/ k -on-season-2-episode-1

    3 Answers · Entertainment & Music · 11/07/2010

  7. k - 1 - 12/( k - 1) = 1 Multiply both sides by k - 1 to get.. k ( k - 1) - k + 1 - 12 = k - 1 k² - k - k - 11 = k - 1 k² - 2k - 11 = k - 1 Bring...

    4 Answers · Science & Mathematics · 28/08/2011

  8. Definitely the K Blade Tour, even though my instructor ...an ease for you to wrist snap on your serves. K Pro is also very head light but its ...

    3 Answers · Sports · 07/12/2008

  9. You could solve k ^2 - 3k + 5 = 0 and plug the two solutions into the second expression... for k . You can, however, use the original equation to simplify the k ^4 expression: k ^4 - 6k^3 + 9k^2 - 7 k ^2( k ^2 - 6k + 9) - 7 k ^2( k ^2 - 3k - 3k...

    4 Answers · Science & Mathematics · 26/11/2008

  1. Ad
    related to: K
  1. Try asking your question on Yahoo Answers